The Role of Military Culture in Therapy and Prevention:Training Recommendations for University and College Counseling Centers. Issue 4 (2nd October 2021) - Ghosh, Arpita; Santana, Mercedes C.; Fox, Troy D.
ABSTRACT: Military culture may affect the psychological functioning of military students who seek services in university and college counseling centers (UCCCs). Further, mental health professionals, including practicum and intern students, working in UCCCs may not be adequately trained to provide multiculturally competent services to military students. Therefore, the purpose of this paper is to provide an overview of military culture from a multicultural framework with military students. First, we present the mental health issues of military students. We then introduce military culture and how that may influence therapy and prevention efforts UCCCs engage in. Lastly, we focus on training recommendations, through didactic instruction and clinical supervision, that UCCCs could employ to assist trainees and their staff to gain competencies needed to work with military students.